Criminal Acts of Murder Committed in Forced Circumstances (Overmacht) - Arrosyiid, Haadi; Febriansyah, Ferry Irawan (International Journal of Law and Society, 2023)
The main objective of this research is to find out what is Forced Circumstances (Overmacht) and why Forced Circumstances (Overmacht) can free perpetrators from criminal responsibility. Departing from here, in conducting research, the author uses normative research methods with a statutory approach (Statue Approach), namely legal research that focuses on examining documents, namely implementing various secondary data such as legal references, statutory regulations, court decisions, and legal theory, and can also be in the form of opinions expressed by legal scholars in processing research. The results of research conducted by the author show that First, Overmacht occurs because the killer does it by first attacking, making his soul vibrate, then defending himself so as not to become a real victim. This was done in self-defence because he had a choice, either he died, or his opponent died. Second, the criminal act of murder under force majeure (overmacht) cannot be held criminally responsible for the perpetrator because, from the start, it is known that it was an act of self-defence (overmacht), and then the investigation must be stopped. If the trial stage continues, the Judge must use his conscience in determining the Judge, and there must be substantial evidence, such as CCTV footage or eyewitnesses from the incident. It can also be based on the actual situation. Criminal liability itself is for a crime, and its purpose is to determine whether a suspect or defendant should be held accountable for a crime that has occurred.